Enhanced Immunogenicity of Chicken H9N2 Influenza Inactivated Vaccine Through a Novel Dual-Targeting Fusion Protein Strategy - Hai Xu; Bihua Deng; Erzhong Wu; Yalu Zhu; Qiurong Qi; Yaming Feng; Yu Lu (Vaccines)
Background/Objectives: Targeted delivery of antigens to dendritic cells (DCs) is an effective strategy for enhancing vaccine efficacy. Methods: In this study, dual-targeting fusion proteins (GRFT-VHH54 and GRFT-VHH74) were constructed by fusing Griffithsin (GRFT), an algae-derived lectin with enveloped virus-binding properties, to DC-specific binding nanobodies (VHH54 and VHH74). Vaccines were formulated by combining the inactivated H9N2 avian influenza virus with these fusion proteins, and the potential of the fusion proteins to enhance vaccine-induced immunity in chickens was systematically evaluated. For parallel comparison, control groups included H9N2 avian influenza vaccines containing the inactivated virus alone, the inactivated virus with the immune enhancer CVCVA5, and a commercial H9N2 avian influenza inactivated vaccine. Results: At 4 weeks post-immunization, chickens vaccinated with the inactivated H9N2 virus combined with the GRFT-VHH74 fusion protein (1/2 H9+GRFT-VHH74) exhibited significantly enhanced humoral, mucosal, and cellular immune responses compared to those vaccinated with the inactivated H9N2 virus alone or the commercial H9N2 vaccine (p < 0.05). Additionally, chickens in the 1/2 H9+GRFT-VHH74 group exhibited enhanced resistance to the heterologous H9N2 subtype avian influenza virus, achieving a 90% protection rate, which was higher than that of the other groups. Conclusions: These results indicate that the GRFT-VHH74 fusion protein has significant potential for advancing the development of inactivated vaccines against the H9N2 subtype avian influenza. Furthermore, it provides valuable insights for enhancing the immunogenicity and efficacy of inactivated vaccines targeting other avian influenza subtypes.